Female University Students' Experiences of Hookah Smoking: Cool Habit and Non-predictable Imminent Consequences and Risks - Ahlam Al- Natour; Gordon. Gillespie (Jordan University of Science and Technology, 2022)
Aim: The purpose of this study is to describe the perceptions of and reasons for adopting Hookah smoking among female university students.  Background: Debates on risk and harm of Hookah smoking existed among female university students.   There is a dearth of studies describing the daily experience and the causative factors for Hookah smoking among female university students.  Methods: A descriptive qualitative design was used for this study. A purposive sample of 14 female university students participated through face-to-face interviews.  Results: The study results included six main themes, Hookah smoking is cool and entertaining, attracting factors for Hookah smoking, Hookah smoking versus Cigarette smoking, sociocultural acceptance for female Hookah Smoking, imminent hazardous consequences of Hookah smoking, and strategies to combat Hookah smoking among females students.  Conclusion: Hookah smoking has become culturally accepted by female university students. Serious attention and initiatives should be considered to enhance female internal awareness to prevent peer pressure to start Hookah smoking. This habit started at home, became accepted by parents, and is now accepted in public places.  Relevance to clinical practice and education: Nurses and policymakers should address the triggering factors for increased Hookah smoking among adults. Nurses should use effective approaches for combating Hookah smoking at different community settings. Also, they should conduct and implement culturally competent preventive programs to combat Hookah smoking in different settings and among all age groups specifically university and school students. Additionally, it is significant to enforce legislations and policies for the prevention of smoking Hookah among adults.